ANALISIS ALASAN PENDAKI MEMILIH PENDAKIAN TEKTOK DAN PENDAKIAN CAMPING - Naufal Rafif Agusti; Sahri (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA (UTP), 2026)
This study aims to analyze the underlying reasons behind hikers' choices in selecting either tektok or camping-style mountain climbing. Tektok hiking refers to a one-day climb without an overnight stay, while camping involves spending one or more nights on the mountain. Each type of hiking offers distinct characteristics, needs, and experiences, making it important to understand the factors that influence hikers' preferences. This research uses a qualitative approach with data collection techniques in the form of in-depth interviews. Informants consisted of six hikers (three tektok hikers and three camping hikers) and one basecamp manager who served as a comparative informant. The study was conducted at the Gunung Andong Via Sawit Basecamp, located in Magelang Regency, Central Java. Thematic analysis was used to identify recurring and meaningful patterns in the data. The findings reveal five main factors influencing hikers’ decisions: personal goals, time constraints, physical condition, logistical preparedness, and financial considerations. Tektok hikers tend to prioritize time efficiency and simplicity of gear, while camping hikers are more motivated by the experience of staying overnight, social interaction, and enjoying a more relaxed atmosphere. Insights from the basecamp manager also indicated a growing trend toward tektok hiking due to busy lifestyles. This study provides deeper understanding of hikers’ preferences within the context of mountain hiking in Indonesia. The results are expected to offer valuable input for basecamp managers to improve service quality and may serve as a reference for future researchers exploring similar phenomena in different locations or settings